PENENTUAN PENERAPAN PRODUKSI BERSIH TERBAIK DI UKM KUE SERABI â€œAPEN JULIT GETTASâ€ KARANGANYAR-SUMENEP DAN ANALISIS NILAI TAMBAHNYA [Determination of the Best Application for Clean Production in the SME of Pancake "Apen Julit Gettas" Karanganyar-Sumenep and Its Value Added Analysis] - Prastika, Yuni Dwi; Ulya, Millatul; Mu'tamar, Mohammad Fuad Fauzul (Jurnal Teknologi & Industri Hasil Pertanian, 2019)
Small and Medium Enterprises (SME) such as the processing of pancakes "Apen Julit Gettas" in Sumenep Regency need to be studied in terms of implementing clean production, because the waste produced is quite large. There are 4 alternative businesses that can be applied for clean production, that are producing animal feed, nata de coco, briquettes, and organic fertilizers. The purpose of this study was to determine the best alternative that would be used for the application of clean production in SME "Apen Julit Gettas" and analyze the added value of the best alternative. The method used to determine the best alternative was the Comparative Performance Index (CPI) and the best alternative value-added analysis using the Hayami method. The best alternative to implementing clean production was processing coconut pulp into animal feed with a value of 285.55. After analyzing added value for coconut pulp industry, the net added value received by the company was Rp. 4,078.64.00/kg with a profit percentage of 53.17%.